The Vicissitudes of Nobles’ Fate: Biography Pages of Nikolai Kisel and Nikolai Meleshko - Потоцький, В'ячеслав (V. N. Karazin Kharkiv National University Bulletin History of Ukraine. Ukrainian Studies: Historical and Philosophical Sciences, 2017)
The article deals with the biography of the Rzeczpospolita army’s officers Nikolai Kisel and Nikolai Meleshko who were killed during the siege of Vinnytsia in 1651. Special attention is paid to their participation in the war against the Cossacks in Ukraine (1648–1657). The article demonstrates that the ways of life of Polish Captains Kisel and Meleshko have much in common. It is likely that these nobles could meet each other before the war against the Cossacks and in those "peaceful" times they belonged to warring factions, which lead a bitter struggle for lands on the territory of the newly created Chernigov voivodeship. During the Khmelnytsky Uprising, these officers could also occur on Election Sejm in 1648, where a new king of Rzeczpospolita was elected.